2005
DOI: 10.1097/01.ta.0000158245.23772.0a
|View full text |Cite
|
Sign up to set email alerts
|

Should Patients with Isolated Hip Fractures Be Included in Trauma Registries?

Abstract: Patients with HIP represented 21.1% of admissions while accounting for 42% of total days of hospitalization and 38% of deaths. Patients with hip fractures have a significantly higher risk of death, prolonged hospital stay, and complication rate, and are more often transferred to a rehabilitation center or to a long-term nursing home than the rest of the trauma population despite lower severity. They require multidisciplinary care typical of the rest of the trauma population and should be included in the trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Similar figures have been reported for other countries in Europe and as the population is growing older the total number of hip fractures is expected to rise 2. Patients suffering hip fractures often have multiple comorbidities and mortality and morbidity is high even though a hip fracture most commonly is a result of a low‐energy trauma 3. Treatment bundles focusing on simple measures to optimize vital organ function, pain relief and early surgical management have been introduced in several countries 4.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Similar figures have been reported for other countries in Europe and as the population is growing older the total number of hip fractures is expected to rise 2. Patients suffering hip fractures often have multiple comorbidities and mortality and morbidity is high even though a hip fracture most commonly is a result of a low‐energy trauma 3. Treatment bundles focusing on simple measures to optimize vital organ function, pain relief and early surgical management have been introduced in several countries 4.…”
Section: Introductionmentioning
confidence: 61%
“…Treatment bundles focusing on simple measures to optimize vital organ function, pain relief and early surgical management have been introduced in several countries 4. Even so current 30‐day mortality for out‐of‐hospital hip fractures is 6%‐10% 3, 5, 6…”
Section: Introductionmentioning
confidence: 99%
“…The NTDB encourages researchers to use inclusion and exclusion criteria in the data registry to create a more homogeneous group; for example, hip fractures should be excluded or analyzed separately, which is also confirmed by Gomez et al [17,18]. In contrast, others argue that elderly with isolated hip fracture should be included in the trauma registry [20]. Elderly with hip fracture comprise currently 17% of the total Dutch trauma population [2].…”
Section: Discussionmentioning
confidence: 96%
“…Of these, 11 (19%) reported that they excluded patients with IHF and were therefore included in our study. [1112131415161718192021]…”
Section: Resultsmentioning
confidence: 99%
“…Included studies were conducted in Canada ( n = 5)[111217181920] or in the United States ( n = 6)[131415161821] [Table 1]. All were retrospective cohort studies published in English between 1993 and 2007.…”
Section: Resultsmentioning
confidence: 99%